PENGARUH SENAM HIPERTENSI TERHADAP TEKANAN DARAH PADA PASIEN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) HIPERTENSI DI UPTD PUSKESMAS BOBOTSARI - Sumiarsih, Sumiarsih; Haniyah, Siti; Safitri, Maya (NHM PRESS, 2024)
Hypertension is defined as elevated blood pressure. It affects the arteries, which are responsible for transporting blood from the heart to other regions of the body. Hypertensive gymnastics is a sport that has been demonstrated to enhance blood flow and oxygen delivery to active muscles and bones, including the heart. This study examined the impact of hypertensive exercises on blood pressure in patients with hypertension prolanis at UPTD Puskesmas Bobotsari. The research design is a one-group pre-test/post-test design with a quasi-experimental approach. The study population consisted of 227 patients diagnosed with hypertension prolanis at UPTD Puskesmas Bobotsari between January and April 2024. A total of 34 respondents were selected using the consecutive sampling technique. This research instrument employs an observation sheet. Bivariate analysis is conducted using a Wilcoxon test. The results of the Wilcoxon test demonstrated a p-value of 0.000, indicating a p-value less than 0.05. Therefore, it can be concluded that there is a statistically significant effect of hypertension gymnastics on blood pressure in hypertension prolanis patients at UPTD Puskesmas Bobotsari.